Endocrine therapies in postmenopausal women with hormone receptor-positive, human epidermal growth factor receptor 2-negative, pretreated, advanced breast cancer: A network meta-analysis. Issue 13 (March 2020) - Lee, Cho-Hao; Kang, Yi-No; Ho, Ching-Liang; Lin, Chin; Chen, Po-Huang; Wu, Yi-Ying; Huang, Tzu-Chuan
Abstract: Background: Recently, many endocrine therapies have become available for hormone receptor-positive, human epidermal growth factor receptor 2-negative, pretreated, advanced breast cancer. Direct comparisons of these novel treatments to assess their added value, however, are lacking Methods: Our aim was to synthesize available evidence to compare all current endocrine treatments for hormone receptor-positive / human epidermal growth factor receptor 2-negative advanced breast cancer. We performed a systematic review to identify available randomized controlled trial evidence. We searched Embase, MEDLINE, and the Cochrane Central Register of Controlled Clinical Trials. Two trials presented at international oncology congresses (American Society of Clinical Oncology [ASCO]) were added to include the most recent evidence. A frequent network meta-analysis was used, and the surface under cumulative ranking area (SUCRA) was calculated to determine the best treatment Results: In total, 32 trials and 12, 726 patients were identified, including 27 arms. Compared with fulvestrant 500 mg alone, novel target inhibitors combined with fulvestrant or exemestane had significantly prolonged progression-free survival with hazard ratios ranging from 0.62 to 0.82. Fulvestrant 500 mg plus palbociclib 125 mg and exemestane 25 mg plus entinostat 5 mg similarly extended progression-free survival (hazard ratio: 0.64 and 0.62 with SUCRA values of 91% and 92%, respectively). The exemestane 25 mg plus everolimus 10 mg combination had the best clinical benefit rate (risk ratio: 1.84, SUCRA: 91%) and overall response rate (risk ratio: 6.05, SUCRA: 97%) Conclusions: On the basis of this analysis, the 2 combinations of exemestane plus everolimus and fulvestrant plus palbociclib were the best treatment options Abstract : Supplemental Digital Content is available in the text